Matured compost amendment improves compost nutrient content by changing the bacterial community during the composting of Chinese herb residues - Song, Xiuchao; Lu, Chao; Luo, Jia; Gong, Xin; Guo, Dejie; Ma, Yan (Frontiers in Microbiology, 2023)
Composting is a sustainable strategy to deal with organic waste. Our research aimed to study the influence of an amendment of 10% matured compost (MC) during Chinese herb residue (CHR) compost. Here, a 60-day CHR compost was performed, and MC application was able to reduce the nitrogen loss and enhance the humic acid accumulation during the composting as compared with the non-inoculated control (NC), by 25% and 19%, respectively. Furthermore, the matured compost amendment improved the diversity of the bacterial community, increased the complexity of the co-occurrence network, and changed the keystone and module hub bacteria during composting. The increased abundance levels of Thermopolyspora, Thermobispora, and Thermosporomyces, which were significantly higher in MC than in NC, may contribute to the degradation of cellulose and the formation of humic acid. Overall, this study extends our understanding of the effects of matured compost reflux on compost quality and the bacterial community.